Analyzing intra-abdominal pressures and outcomes in patients undergoing laparotomy - Daga, Sharad; Yerrapragada, Srinivas; Chowdary, Amirineni Krishna; Satyanarayana, G. (International Surgery Journal, 2016)
Background:Despite the abundance of knowledge, IAH still remains strangely under-diagnosed. A national postal questionnaire in United Kingdom reported that despite widespread awareness of IAH and the ACS, many intensive care units never measure the IAP. The aim was to evaluate the effects of intra-abdominal hypertension and to assess whether intra-abdominal pressure is a predictor of morbidity and mortality in patients undergoing laparotomy. Methods: This was a prospective observational study conducted in Department of General Surgery, Kamineni Hospitals, L. B. Nagar, Hyderabad, India on patients undergoing emergency and elective laparotomy, over a period of 2 years from October 2012 to October 2014. The study included 51 patients who underwent laparotomy. IAP was measured preoperatively and then post-operatively at 0, 6, 24, 48 and 72 hours. If IAP remained below 12 mmHg, measurement was discontinued after 24 hours. Duration of ICU and hospital stay, occurrence of burst abdomen, new organ function damage, need for ventilatory support and mortality in patients undergoing laparotomy were noted as outcomes. Results:At admission, an overall 65% incidence of intra-abdominal hypertension (IAH) was observed. In this group of 33 patients, CVS dysfunction was seen in 11 patients (33.3%), Respiratory dysfunction was seen in 9 patients (27.2%) and renal dysfunction was seen in 11 patients (33.3%). At 24 hours improvement was seen in all organ dysfunctions. Number of patients with CVS, respiratory and renal dysfunction in this group of 33 patients at 24 hours was 5 (15%), 4 (12%) and 6 (18%) respectively. This signifies that along with decrease in incidence of IAH, there is concomitant decrease in incidence of organ dysfunctions and morbidity. Conclusions:Raised intra-abdominal pressure (IAP) is associated with higher morbidity and mortality in patients undergoing laparotomy. Intra-abdominal hypertension (IAH) has detrimental effect on various organ systems and decompression leads to improvement in all the parameters.